(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The world’s largest tribal population, found in around 15 of India’s land area, inhabits a variety of ecological and geoclimatic settings, from plains to hills remote regions. This paper undertakes a critical examination of skill development programs implemented by governments for tribal communities. Recognizing the imperative to bridge socio-economic disparities and empower marginalized groups, governments worldwide have initiated various skill development schemes aimed at uplifting tribal populations. The history of tribal development administration is extensive. Even though India was a colony at the time, it all began then. The administration of tribal development has evolved throughout time in response to changes in the Scheduled Areas people that inhabit them. Many skill-building programmes specifically target tribal communities, and most broad-based efforts prioritise serving tribal people.